Influence of Family Support on the Implementation of Hypertension Monitoring in Banjarmasin (Proceedings OPTIMAL, 2025)
Background: Hypertension can be prevented by management and monitoring a risk factors like a habitual of smoking, consuming excessive salt, alcoholic beverages, obesity, lack of physical activity, and stres.  One of the efforts to manage hypertension needs family participation to support its monitoring. Purpose: This study aims to determine the relationship between family support and the process of monitoring hypertension in Banjarmasin in 2023. Methods: This study is a quantitative research with a cross-sectional design using a questionnaire for family support and an observation sheet to assess hypertension monitoring. The research period was from May 2023 to June 2023. There are 199 respondent that selected by purposive sampling. Data analysis was performed using the chi-square test at ɑ = 0.05. Result: The results of the Chi-square analysis test obtained the P value is 0.460, more significant than the value of 0.05, which means that that Ha is rejected and Ho is accepted, where there is no relationship of family support for monitoring hypertension treatment. Conclusion: There is no relationship between a family support to hypertension monitoring compliance in the work area in Banjarmasin. The result shows that most of the family support has been done well and it must be accompanied by the implementation of family functions. For health workers as health service providers can participate in carrying out promotive actions Involving the family